Randomized cross-over trial of demand oxygen delivery system in nocturnal hypoxemia. Issue 19 (May 2020) - Nagano, Tatsuya; Kobayashi, Kazuyuki; Omori, Takashi; Otoshi, Takehiro; Umezawa, Kanoko; Katsurada, Naoko; Yamamoto, Masatsugu; Tachihara, Motoko; Nishimura, Yoshihiro
Abstract: Background: It has not been determined that demand valve oxygen therapy is effective for nocturnal hypoxia. A portable oxygen concentrator with an auto-demand oxygen delivery system (auto-DODS; standard, high, and extra high) has recently been developed to improve oxygenation and comfort. This oxygen concentrator can supply a pulsed flow when it detects apnoea. The aim of this study is to demonstrate that this newly developed portable oxygen concentrator with an auto-demand function is non-inferior to a continuous-flow oxygen concentrator for nocturnal hypoxemia. Methods: Twenty patients with chronic obstructive pulmonary disease or interstitial pneumonia will be randomized to receive a portable oxygen concentrator with an auto-DODS or a continuous-flow oxygen concentrator during sleep. The primary endpoint is mean oxygen saturation (SpO2 ) during the total sleep time. The secondary endpoints are the ratios of time that the oxygen concentrator spends in each sensitivity mode (standard, high, and extra-high) and at a constant pulse rate to the total sleep time, the total time and ratio of time for which SpO2 is less than 90% during the total sleep time, the lowest value of SpO2 during the total sleep time, the mean and highest pulse rate during the total sleep time, the apnoea index during the total sleep time, the total sleep duration itself, and comfort and reliability as measured by numerical rating scale and questionnaires. Discussion: If the auto-DODS demonstrates non-inferiority to continuous flow in oxygenation during sleep, the auto-DODS can be used even at night, and the patient will need only 1 device. Trial Registration: The study was registered on Aug 23, 2019 (jRCTs052190042).